Sex‐dependent and sex‐independent regulatory systems of size variation in natural populations - Hirokazu Okada; Ryohei Yagi; Vincent Gardeux; Bart Deplancke; Ernst Hafen (Molecular Systems Biology)
Abstract Size of organs/organisms is a polygenic trait. Many of the growth‐regulatory genes constitute conserved growth signaling pathways. However, how these multiple genes are orchestrated at the systems level to attain the natural variation in size including sexual size dimorphism is mostly unknown. Here we take a multi‐layered systems omics approach to study size variation in the Drosophila wing. We show that expression levels of many critical growth regulators such as Wnt and TGFβ pathway components significantly differ between sexes but not between lines exhibiting size differences within each sex, suggesting a primary role of these regulators in sexual size dimorphism. Only a few growth genes including a receptor of steroid hormone ecdysone exhibit association with between‐line size differences. In contrast, we find that between‐line size variation is largely regulated by genes with a diverse range of cellular functions, most of which have never been implicated in growth. In addition, we show that expression quantitative trait loci (eQTLs) linked to these novel growth regulators accurately predict population‐wide, between‐line wing size variation. In summary, our study unveils differential gene regulatory systems that control wing size variation between and within sexes.